2020
DOI: 10.1186/s12870-020-02377-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs associated with curd architecture in cauliflower

Abstract: Background: Curd architecture is one of the most important characters determining the curd morphology of cauliflower. However, the genetic mechanism dissection of this complex trait at molecular level is lacking. Genes/ QTLs responsible for the morphological differences between present-day loose-curd and compact-curd cauliflower haven't been well revealed. Results: Herein, by using a common compact-curd parent and two loose-curd parents, we developed two double haploid (DH) populations including 122 and 79 lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The result that these QTLs associated with different traits were co-located might be attributed to one same QTL, a gene multi-effect, or two QTLs closely linked, therefore leading to the correlation among morphological traits. Similar colocalizing QTLs were also observed in other plants such as prunus mume [43,44], rice [45], wheat [46,47], sesame [48], cauliflower [49], barley, and so on [50]. However, whether the co-localized QTLs are single-gene with pleiotropism or are just closely linked but distinct genes in our results remains to be further studied.…”
Section: Qtls Related To Morphological Traitssupporting
confidence: 85%
“…The result that these QTLs associated with different traits were co-located might be attributed to one same QTL, a gene multi-effect, or two QTLs closely linked, therefore leading to the correlation among morphological traits. Similar colocalizing QTLs were also observed in other plants such as prunus mume [43,44], rice [45], wheat [46,47], sesame [48], cauliflower [49], barley, and so on [50]. However, whether the co-localized QTLs are single-gene with pleiotropism or are just closely linked but distinct genes in our results remains to be further studied.…”
Section: Qtls Related To Morphological Traitssupporting
confidence: 85%
“…Overall, these results can be explained based on NBC-mediated improvements in physio-biochemical traits and the presence of growth-promoting substances. Curd architecture is mainly determined by polygenetic factors, although also influenced by environmental conditions such as nutrient availability [70]. Metwaly [71] reported that the P and K influenced the curd morphological traits and curd compactness.…”
Section: Enhancement In Yield and Architectural Traits Through Synerg...mentioning
confidence: 99%
“…To facilitate the breeding of cauliflower, some studies have tried to detect genomic loci for its agronomic traits. Zhao et al [10] performed a mapping of quantitative trait loci (QTLs) by using two double-haploid (DH) populations, and they identified 20 QTLs for curd architecture, including stalk length (qSL.C6-1, qSL.C6-2) and curd solidity (qCS.C6-1 and qCS.C6-2). Hasan et al [11] detected QTL regions that were involved in the temperaturedependent time to curd induction, on chromosomes C06 and C09.…”
Section: Introductionmentioning
confidence: 99%